The Legal Position of National Minorities and the Formation of State in Years’20 - Cobo, Marenglen (European Journal of Multidisciplinary Studies, 2016)
Albania came out of World War I in an economic – political difficult situation. State institutions lack of consolidation and the difficult living conditions in which was the population, adding even more the future uncertainty of this small state. Furthermore, Albania is not yet recognized by other states and the League of Nations as an independent state with full and equal rights. This small state during the years 20 ’ occupied an area of 27,539. 10 km2 and had a population of 803 959 inhabitants. As belonged to the territorial organization and administrative division, it was divided in 9 prefectures, 31 sub-prefectures and 80 provinces. Its population belonged to three different religious faiths: Muslim, Catholic and Orthodox. The number of residents who claimed to belong to the religion of Islam was about 529,694, and those who belonged to the Orthodox religion were 168 215 and those who belonged to the Catholic religion were 96,050 . But related to the ethnic composition of the population, the Albanian state is presented as homogeneouswhere national minorities occupied a small percentage, no more than 10 percent. The small presence of minority in Albanian territory probably was also one of the reasons that explain the reason for the lack of labor conflicts with ethnic character. Minorities that were identified as non-Albanian minorities were divided into ethno-cultural and national minorities. In the first group were included Rom and Vlachs, while on the second group were included: Montenegrin minorities, Macedonian and Greek national minorities.